Telecommunications Infrastructure in the Arctic; A Circumpolar Assessment - Arctic Council Task Force on Telecommunications Infrastructure in the Arctic (Arctic Council Secretariat, 2017)
This report presents the Task Forces investigation and analysis into the technologies presently available to users, and identifies gaps in the infrastructure. The report also provides an overview of each State's telecommunications priorities. Changes occur rapidly in the telecommunications industry, and it is inevitable that some of the information or details contained in this report will quickly become outdated. Readers should view this report as a "snapshot" of the state of telecommunications infrastructure in the Arctic, and should certainly be attentive to ongoing developments. The Task Force on Telecommunications Infrastructure in the Arctic (TFTIA) was established by Ministers of the Arctic States at the 2015 Arctic Council Ministerial meeting in Iqaluit. From 2015-2017, the TFTIA worked to assemble and assess information about the available telecommunications infrastructure in the Arctic and the present-day needs of users living, working, or traveling in the Arctic.